Strengthening the development impact of UNCTAD's investment policy reviews - Jungnickel, Rolf; Koopmann, Georg (2005)
Abstract: "1. IPRs can be a very useful instrument for making FDI policy more effective for the development process. 2. IPRs should not focus exclusively on foreign direct investment but rather on investment in general and consider FDI as one of several elements in the development process. 3. UNCTAD should, in accord with donor countries, take a greater say in the selection of the countries reviewed. The starting point should be an analysis of the absorption capacity and the need for external assistance in the countries in question. 4. In view of widely differing domestic capacities and different needs for and institutional policy advice, UNCTAD should undertake more efforts to adapt the volume of issues covered to the advice actually needed. Activities could extend from Quick Response Window action on one or few specific problems to an "IPR light" or a full-fledged IPR. 5. Recommendations should be based more on investors' and non-investors' experiences and assessments than on a formal inve